Anatomical and functional changes in the organization of the cuneate nucleus of adult rats after fetal forelimb amputation - Rhoades, RW (J Neurosci, 1993)
A previous study has shown that fetal forelimb removal in the rat results in an increase in the size of the hindlimb representation in primary somatosensory cortex and suggested that this anomalous cortical organization may have resulted from alterations in the primary afferent innervation of the dorsal column nuclei (Killackey and Dawson, 1989). The present study used both anatomical and electrophysiological techniques to examine the effects of fetal forelimb amputation on the dorsal column nuclei. Rats sustained forelimb removals on embryonic day 16 and were used in terminal experiments when they reached adulthood (> 60 d of age). Analysis of cytochrome oxidase-stained sections demonstrated that the cuneate nucleus ipsilateral to the lesion decreased in volume by an average of 36.7% (N = 7, p < 0.001, paired t test), but there was no corresponding increase in the volume of the gracile fasciculus and nucleus. Bilateral application of HRP to the sciatic nerves demonstrated that axons that innervate only the gracile nucleus on the intact side of the brainstem were present in the cuneate nucleus on the deafferented side. Injection of HRP into the skin overlying the point of the amputation (the stump) indicated that axons innervating this region filled most of the dorsal one-half of the shrunken cuneate nucleus and overlapped with the sciatic nerve afferents innervating the cuneate on this side. Mapping the receptive fields of multiple unit clusters demonstrated that most recording sites in the shrunken cuneate nucleus were activated by inputs from the stump and adjacent skin. In addition, 9.1% (N = 30) of such unit clusters (N = 328) could also be excited by stimulation of the hindlimb. These were observed in only three of the nine experiments. Unit clusters with split receptive fields including the skin overlying the stump and the hindlimb were located throughout the rostrocaudal extent of the cuneate nucleus. These results indicate that fetal forelimb amputation results in anatomical expansion of the central projections of hindlimb afferents into the cuneate nucleus. This anatomical organization appears weakly expressed in the receptive fields of cuneate neurons.